Physician Adherence to Guideline Recommendations for Mild COVID-19 in Peru: A Cross-sectional Study - Wong, Kiamfun (2024)
Objective: To examine the factors associated with Peruvian physicians' adherence to guidelines for managing mild COVID-19 cases. Methods: An analytical cross-sectional study was conducted, surveying certified Peruvian physicians from different regions. A simulated clinical case was used to evaluate their knowledge of the pharmacological management of mild COVID-19 and the potential adverse effects of prescribed medications. Adherence to guidelines was defined as prescribing only acetaminophen and/or non-steroidal anti-inflammatory drugs (NSAIDs) for the proposed mild COVID-19 case, in accordance with international recommendations. Factors associated with adherence were analyzed using prevalence ratios, calculated through Poisson regression with robust variance. Results: A total of 339 physicians participated, 85.0% of whom adhered to the recommended guideline. The most frequently prescribed drugs were acetaminophen (96.2%), non-steroidal anti-inflammatory drugs (11.5%), and ivermectin (6.8%). Physicians who graduated from private universities exhibited greater adherence to the guidelines (PR: 1.14; 95% CI 1.05-1.23), while those affiliated with the Ministry of Health (MINSA) demonstrated lower adherence (PR: 0.87; 95% CI: 0.79-0.84). Conclusion: Most physicians adhered to the guidelines for managing mild COVID-19. Higher adherence was associated with graduating from private universities and working outside MINSA affiliated institutions.